2018
DOI: 10.1063/1.5021292
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of flexible fluorescent films prepared by screen printing technology

Abstract: In this work, we prepared a fluorescent film comprised phosphors and silicone on flexible polyethylene terephthalate (PET) substrate using a screen printing technology. The effects of mesh number and weight ratio of phosphors to silicone on the optical properties of the flexible films were investigated. The results indicate that the emission intensity of the film increase as the mesh decreased from 400 to 200, but the film surface gradually becomes uneven. The fluorescent film with high emission intensity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…13 Moreover, luminescence films can be deposited on both rigid and flexible substrates, opening up new application fields. 14,15 Usually, screenprinting is implemented to produce films of micrometer thickness; some studies have demonstrated the possibility of deposition of submicron films by tuning the printing pastes. 16 However, the study of an economical way to fabricate NIR luminescent films by screen printing is far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…13 Moreover, luminescence films can be deposited on both rigid and flexible substrates, opening up new application fields. 14,15 Usually, screenprinting is implemented to produce films of micrometer thickness; some studies have demonstrated the possibility of deposition of submicron films by tuning the printing pastes. 16 However, the study of an economical way to fabricate NIR luminescent films by screen printing is far from complete.…”
Section: Introductionmentioning
confidence: 99%